The European Green Deal and the Opportunities and Risks of Organic Farming in Poland - Hajdys, Dagmara (Journal of Finance and Financial Law, 2024)
The purpose of the article. The aim of the study is to identify the key assumptions of the European Green Deal strategy with regard to organic farming. Special attention was paid to the opportunities and risks of the transition to "green" agriculture in Poland. It is assumed that the transition to organic farming in Poland will require a change in the architecture of agriculture with the development of a compromise between environmental and sectoral needs.Methodology. The article is a review and the following research methods were used to achieve the intended purpose: a review of the literature on the subject, EU regulations and statistical data on agriculture, including organic agriculture in Poland, the descriptive and inductive method.Results of the research. The European Green Deal is an ambitious strategy for the European Union to meet today's economic, social and, above all, environmental challenges. The main objectives of the document are to achieve zero greenhouse gas emissions by 2050, to decouple economic growth from the overexploitation of natural resources, to move towards a clean circular economy, to combat biodiversity loss and to reduce pollutant emissions. All of these goals are directly or indirectly related to the agricultural sector. Two strategies are particularly relevant to this sector: "From Field to Fork" and the EU Biodiversity Strategy 2030. Agriculture in Poland is changing. Despite the gradual transition from conventional to organic farming, the dynamics of the transformation are unsatisfactory. A characteristic feature of organic farms is their commodity nature, with a predominance of crop production. Farms specialising in livestock or mixed farming are a small percentage. The European Green Deal brings both opportunities and threats for Polish organic farming. The reduction of greenhouse gas emissions and healthy food for consumers are undoubtedly benefits of the proposed changes. There are also dangers of an economic nature. Those in power have a huge responsibility to adopt solutions that reconcile environmental and social interests.